The physicochemical and biomechanical profile of forsterite and its osteogenic potential of mesenchymal stromal cells. - Genasan Krishnamurithy; Saktiswaren Mohan; Noor Azlin Yahya; Azura Mansor; Malliga Raman Murali; Hanumantha Rao Balaji Raghavendran; Rajan Choudhary; Swamiappan Sasikumar; Tunku Kamarul (PLoS ONE, 2019)
It has been demonstrated that nanocrystalline forsterite powder synthesised using urea as a fuel in sol-gel combustion method had produced a pure forsterite (FU) and possessed superior bioactive characteristics such as bone apatite formation and antibacterial properties. In the present study, 3D-scaffold was fabricated using nanocrystalline forsterite powder in polymer sponge method. The FU scaffold was used in investigating the physicochemical, biomechanics, cell attachment, in vitro biocompatibility and osteogenic differentiation properties. For physicochemical characterisation, Fourier-transform infrared spectroscopy (FTIR), Energy dispersive X-ray (EDX), X-ray diffraction (XRD), Raman spectroscopy, X-ray photoemission spectrometer (XPS) and Brunauer-Emmett-Teller (BET) were used. FTIR, EDX, XRD peaks and Raman spectroscopy demonstrated correlating to FU. The XPS confirmed the surface chemistry associating to FU. The BET revealed FU scaffold surface area of 12.67 m2/g and total pore size of 0.03 cm3/g. Compressive strength of the FU scaffold was found to be 27.18 ± 13.4 MPa. The human bone marrow derived mesenchymal stromal cells (hBMSCs) characterisation prior to perform seeding on FU scaffold verified the stromal cell phenotypic and lineage commitments. SEM, confocal images and presto blue viability assay suggested good cell attachment and proliferation of hBMSCs on FU scaffold and comparable to a commercial bone substitutes (cBS). Osteogenic proteins and gene expression from day 7 onward indicated FU scaffold had a significant osteogenic potential (p<0.05), when compared with day 1 as well as between FU and cBS. These findings suggest that FU scaffold has a greater potential for use in orthopaedic and/or orthodontic applications.